How Opportunities Develop in Social Entrepreneurship - Corner, Patricia Doyle; Ho, Marcus (Entrepreneurship Theory and Practice, 2010)
The purpose of this article was to extend existing research on opportunity identification in the social entrepreneurship literature through empirically examining this phenomenon. We used an inductive, theory–building design that surfaced patterns in social value creation across multiple case studies. The patterns showed actors seeing a social need and prospecting ideas that could address it. Data also revealed multiple, not individual, actors, dynamically engaged in interactions that nudged an opportunity into manifestation. Also, data suggested complementarities to effectuation and rational/economic processes that are divergent theoretical approaches to the study of entrepreneurship to date.